(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
Detective literature thrives on suspense, intrigue, and the art of storytelling, where every word contributes to the overall narrative. Among the various linguistic tools available to authors, phraseological units—fixed expressions or idiomatic phrases—play a crucial role in enriching the text. This article delves into the multifaceted functions of phraseological units in detective literature, examining how they create atmosphere, develop characters, enhance dialogue, foreshadow events, and engage readers. By analyzing specific examples and their implications within the genre, we uncover the deeper significance of these expressions in shaping the reader’s experience and enhancing the storytelling craft. Ultimately, this exploration reveals that phraseological units are not mere embellishments; they are essential components that contribute to the richness and depth of detective narratives.